2024
DOI: 10.3389/fcell.2024.1337361
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression patterns of cancer associated fibroblast markers reveal distinct subgroups related to patient survival in oropharyngeal squamous cell carcinoma

Su Ir Lyu,
Jannik Johannsen,
Adrian Georg Simon
et al.

Abstract: Background: The incidence of oropharyngeal squamous cell carcinoma (OPSCC) is rapidly increasing in high income countries due to its association with persistent high-risk human papilloma virus (HPV) infection. Recent scientific advances have highlighted the importance of the tumor microenvironment in OPSCC. In this study, including 216 OPSCC patients, we analyze the composition of four established markers of cancer associated fibroblasts (CAFs) in the context of intratumoral CD8 T-cell infiltration.Methods: Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Some studies have revealed that the higher the content of CAFs, the worse the prognosis of HNSCC patients [ 37 , 51 ]; however, it has also been shown that the content of CAFs has no significant association with the prognosis of HPV-positive HNSCC patients [ 52 ]. This contradiction may be related to the different measurement methods and standards used.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have revealed that the higher the content of CAFs, the worse the prognosis of HNSCC patients [ 37 , 51 ]; however, it has also been shown that the content of CAFs has no significant association with the prognosis of HPV-positive HNSCC patients [ 52 ]. This contradiction may be related to the different measurement methods and standards used.…”
Section: Discussionmentioning
confidence: 99%